ASPECTS OF MODERN ETHNIC SITUATION IN GEORGIA: PROBLEMS OF MINORITY GROUPS (BEZHTINTSY CASE) - M. Sh. Sheikhov (Юг России: экология, развитие)
The article examined the current socio-economic status of one of the ethnicities of Dagestan - bezhtintsev that after the collapse of the Soviet Union were on their lands in a "foreign" country. The problems faced by bezhtintsy in Georgia and offered a way out.